A HISTORICAL STUDY ON DIFFERENT TYPES OF TEMPLE TOURISM IN INDIAN CONTEXT (International Journal of Food and Nutritional Sciences, 2023)
The temple had an enduring ideological importance in the history of any land. It is said that Temples are the off-springs of respective Religions. Temples are a central focus of historical processes like social, religious, economic and political. Earlier, the temples acted as legitimating institutions of the rulers, especially the king in particular. The king acquired legitimacy and tried to convey the authority through the temple and its symbolism. Temple acted as an integrating force for organizing a well-developed society. It is worth noting that even the temple was connected to this ruling elite and was the integral process to the above link, it was inseparably linked to the development of the sectarian traditions, religion, society, economy and the polity.